Develop Empowerment Whatsapp Group to Increase Optimism of Breast Cancer Survivors - Namora Lumongga Lubis; Hasnida Hasnida; Lilis Novitarum (Global Health Science Group, 2021)
Breast cancer patients must undergo a series of therapies that take a long time with painful side effects. Fellow breast cancer sufferers are people who can provide psychological support to patients. Cancer patients need to get support from others to always motivate, encourage, motivate, control and assist cancer patients. Objective: This study aims to develop a model of empowerment of WhatsApp Group to Increase Optimism of Breast Cancer Survivors in Medan. Method: The type of research used is action research with 72 sample. There are 2 types of instruments for data collection, the focus group discussion (FGD) question guide and the Revised Life Orientation Test (LOT-R) instrument with cronbach alpha 0.95. The increase in optimism can be seen from the average score of optimism before and after research. Results: This research in the formation of the Whattsapps Group HFCC Community Group for posting positive things in the group. The results of the optimism assessment showed that 83% of participants had positive optimism after the webinar activity on tips and tricks